2019
DOI: 10.3390/jmse7040120
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Viscous Drag for a Domed Cylindrical Moored Wave Energy Converter

Abstract: Viscous drag, nonlinear in nature, is an important aspect of the fluid–structure interaction modelling and is usually not taken into account when the fluid is assumed to be inviscid. Potential flow solvers can competently compute radiation damping, which is related to the radiated wave field. However, the drag damping primarily related to the viscous effects is usually neglected in the radiation/diffraction problems solved by the boundary element method (BEM), also known as the boundary integral element method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The WEC consists of two rigid bodies connected with two vertical tendons. The first body is a fully submerged horizontal cylinder with domed ends and rectangular-shaped surface piercing columns, while the second one is a fully submerged mass [36,37]. A system of mooring lines is used to keep the WEC in place by providing horizontal and heave stiffness.…”
Section: Resultsmentioning
confidence: 99%
“…The WEC consists of two rigid bodies connected with two vertical tendons. The first body is a fully submerged horizontal cylinder with domed ends and rectangular-shaped surface piercing columns, while the second one is a fully submerged mass [36,37]. A system of mooring lines is used to keep the WEC in place by providing horizontal and heave stiffness.…”
Section: Resultsmentioning
confidence: 99%
“…An effective approach to overcome the scaling issue is to perform full-scale experiments using RANS simulations, as demonstrated in [17,[210][211][212][213][214][215][216]. The discrepancies in drag coefficient values and methods to calculate them for a spherical HPA is investigated in Giorgi and Ringwood [217], where it is concluded that estimating the drag coefficient is challenging, resulting in uncertainties and inconsistencies in reported values for the same geometry in different publications.…”
Section: Viscous Force Termmentioning
confidence: 99%
“…Numerical codes based on the potential flow theory are also frequently used to evaluate the performance of point-absorber-type WECs [9][10][11], and discrepancies in motions are often noted between the numerical and experimental results for motion. This issue is attributed to the absence of viscous effects in such numerical models [12,13], in which the assumption of zero viscosity in the fluid can lead to over-estimation of the motions for bodies when the pressure and skin friction drag from viscous effects is significant.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, the region surrounding the resonant frequency is most influenced by the viscous effects [14]. Accurate modelling of the motions about the natural periods is important, and several investigations have sought to mitigate the effects of viscous damping by tuning the numerical models [9,10,15,16]. A common approach taken in potential flow investigations is to incorporate an external, frequency-independent damping force that is linearly proportional to the structure's displacement or rotational velocity; some examples include the simulation of side-by-side vessel motions [15] and multiple point absorber WECs integrated into a floating platform [16].…”
Section: Introductionmentioning
confidence: 99%